HPF1 completes the PARP active site for DNA damage-induced ADP-ribosylation - Suskiewicz, MJ; Zobel, F; Ogden, TEH; Fontana, P; Ariza, A; Yang, J-C; Zhu, K; Bracken, L; Hawthorne, WJ; Ahel, D; Neuhaus, D; Ahel, I (Springer Nature, 2020)
The anti-cancer drug target poly(ADP-ribose) polymerase 1 (PARP1) and its close homologue, PARP2, are early responders to DNA damage in human cells1,2. Upon binding to genomic lesions, these enzymes utilise NAD+ to modify a plethora of proteins with mono- and poly(ADP-ribose) signals that are important for subsequent chromatin decompaction and repair factor recruitment3,4. These post-translational modification events are predominantly serine-linked and require HPF1, an accessory factor that is specific for the DNA damage response and switches the amino-acid specificity of PARP1/2 from aspartate/glutamate to serine residues5–10. Here, we report a co-structure of HPF1 bound to the catalytic domain of PARP2 that, in combination with NMR and biochemical data, reveals a composite active site formed by residues from both PARP1/2 and HPF1. We further show that the assembly of this new catalytic centre is essential for DNA damage-induced protein ADP-ribosylation in human cells. In response to DNA damage and NAD+ binding site occupancy, the HPF1–PARP1/2 interaction is enhanced via allosteric networks operating within PARP1/2, providing an additional level of regulation in DNA repair induction. As HPF1 forms a joint active site with PARP1/2, our data implicate HPF1 as an important determinant of the response to clinical PARP inhibitors.